2014
DOI: 10.15244/pjoes/26779
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of 4-Chloro-2-Nitrophenol from Aqueous Solution by Graphene Adsorption: Equilibrium, Kinetic, and Thermodynamic Studies

Abstract: Phenol and its compounds are one of the major materials commonly used in the petrochemical, coking, coal refining, chemical, and pharmaceutical industries [1,2]. The harmful effects due to the presence of phenols in industrial wastewaters have been confirmed [3,4]. Thus, development of suitable methods for the decontamination of phenols is necessary. Research has studied the removal of phenol from aqueous solutions, including advanced oxidation processes [5,6], biological degradation [7,8], ozonation [9,10], a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Therefore, graphene oxide was selected-an effective candidate of the carbon family-due to its exceptional structure (2-D, one-atom-thick structure), superior mechanical qualities, and total surface area for chitosan modification (Sayed et al 2022c). Graphene oxide (GO) has been widely employed to eliminate metal ions, dyes, and other contaminants (Gad and Nasef 2021, Kameli and Mehrizad 2019, Mehrizad and Gharbani 2014. The chitosan-GO grafted materials were nominated due to functional group variation (OH, H, CO, and NH 2 ) in the composite matrix, which can interact with many pollutants in different ways Jiang 2016, Zhao et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, graphene oxide was selected-an effective candidate of the carbon family-due to its exceptional structure (2-D, one-atom-thick structure), superior mechanical qualities, and total surface area for chitosan modification (Sayed et al 2022c). Graphene oxide (GO) has been widely employed to eliminate metal ions, dyes, and other contaminants (Gad and Nasef 2021, Kameli and Mehrizad 2019, Mehrizad and Gharbani 2014. The chitosan-GO grafted materials were nominated due to functional group variation (OH, H, CO, and NH 2 ) in the composite matrix, which can interact with many pollutants in different ways Jiang 2016, Zhao et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Others phenolic compounds have been studied through of the adsorption process with carbon materials. Mehrizad and Gharbani [58] used rGO as adsorbent for the removal of 4-Chloro-2nitrophenol (4C2NP) from aqueous solutions. The adsorption capacity of rGO onto 4C2NP removal decreased with increasing dosage of adsorbent from 0.2 to 0.8 g/L but in all cases the adsorption velocity was rapid (10 min) reaching the equilibrium at about 60 min.…”
Section: Carbon-based Materials (Activated Carbon and Nanomaterials)mentioning
confidence: 99%
“…Thermodynamic study showed that adsorption of phenol onto RGO was endothermic and spontaneous process. In other work, the removal of 4-Chloro-2-nitrophenol (4C2NP) from aqueous solutions was performed using graphene as adsorbent [58]. Effect of the pH solution, contact time, initial concentration and temperature on the adsorption of 4C2NP onto GE was studied.…”
Section: Graphene and Graphene Oxide As Adsorbent Of Organic Pollutanmentioning
confidence: 99%